2008
DOI: 10.1038/sj.npp.1301672
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Low-Dose Naloxone Restores the Antinociceptive Effect of Morphine and Suppresses Spinal Neuroinflammation in PTX-Treated Rats

Abstract: The aim of the present study was to examine the effect of ultra-low-dose naloxone on pertussis toxin (PTX)-induced thermal hyperalgesia in rats and its underlying mechanisms. Male Wistar rats, implanted with an intrathecal catheter with or without a microdialysis probe, received a single intrathecal injection of PTX (1 mg in 5 ml saline). Four days after PTX injection, they were randomly given a different dose of naloxone (either 15 mg or 15 ng in 5 ml saline), followed by a morphine injection (10 mg in 5 ml s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…One study has demonstrated the efficacy of NMDAR antagonists for preventing OIH (Minville et al, 2010). Furthermore, a number of investigations found that clinical doses of naloxone antagonize opioid effects, whereas ultra-low doses enhance the antinociceptive effects of morphine (Tsai et al, 2008;Yang et al, 2011). In this study, we investigated the relationships among the GluN1 subunit, opioids, and OIH in search of an effective method to treat OIH.…”
Section: Introductionmentioning
confidence: 99%
“…One study has demonstrated the efficacy of NMDAR antagonists for preventing OIH (Minville et al, 2010). Furthermore, a number of investigations found that clinical doses of naloxone antagonize opioid effects, whereas ultra-low doses enhance the antinociceptive effects of morphine (Tsai et al, 2008;Yang et al, 2011). In this study, we investigated the relationships among the GluN1 subunit, opioids, and OIH in search of an effective method to treat OIH.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-low dose naloxone suppresses microglia activation and induces IL-10 expression in spinal neuron and microglia in PTX-treated rats As in our previous study (Tsai et al, 2008(Tsai et al, , 2009b, weak immunostaining was observed in resting microglia (Fig. 1A).…”
Section: Resultsmentioning
confidence: 51%
“…In our previous studies, intrathecal administration of ultra-low dose naloxone restored the antinociceptive effect of morphine, revered the coupling of μ-opioid receptors from Gs-protein to Gi-protein (Tsai et al, 2009a), suppressed microglia activation, inhibited the expression of IL-1β, IL-6, and phosphorylated p38 (P-p38) mitogen-activated protein kinase (MAPK) (Tsai et al, 2008(Tsai et al, , 2009b in PTX-treated rats. However, the anti-inflammation mechanisms of ultra-low dose naloxone remain unclear.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The concentrations of EAAs were measured by phenylisothiocyanate derivatization using a high-performance liquid chromatography (Agilent 1100; Agilent Technologies, Santa Clara, CA) with a reversedphase ZORBAX Eclipse amino acid analysis column (4.6 ϫ 150 mm 2 , 3.5 M) and fluorescent detector (Gilson model 121, set at 428 nm), as described previously. 25 External standards (authentic amino acids at concentrations of 156.25, 312.5, 625, 1,250, and 2,500 M) were run at the beginning and end of each sample group. Peak heights were normalized to the standard peaks and quantified based on the linear relationship between peak height and the amount of the corresponding standard.…”
Section: Cerebrospinal Fluid Sample Collection and Measurement Of Excmentioning
confidence: 99%